A Constituição da República Federativa do Brasil e o direito fundamental à segurança pública - Safi, Dalton Abranches (2018)
The present research aims to investigate the treatment of public safety on the Constitution of the Federative Republic of Brazil, which was promulgated on the 5th of October, 1988. We will firstly explore themes that are closely connected to the main one. It begins with the analysis of fundamental rights, with attention to their importance and meaning, starting to relate these rights with matters pertaining to State, Constitution and democracy, as well as its indelible imbrication with the principle of the Dignity of the Human Person. Fundamental rights are bundled with the demonstration of their dual nature. The research, therefore, aims to analyze the current Federal Constitution, an opportunity in which it seeks to discuss a general panorama of this normative document, with a focus on security and public safety. At the end, we try to address the nodal question of the research, with the verification of the legal nature of public security on the Citizen Constitution. It is therefore possible to ascertain whether the status of public security in the Major Law is that of a fundamental right, being defended assertively, also referring to the relevance of such categorization and in which dimension of fundamental right public security it is inserted